Analisis Findtech (Byond) Pada Kepuasan Nasabah Bank Syariah Indonesia di Jl. Panglima Sudirman No.177 Kota Pasuruan - Nisa Alfi Syahrin; M. Dayat; Ifdlolul Maghfur (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study analyzes the effect of usage effectiveness and service quality of the BYOND by BSI application on customer satisfaction at Bank Syariah Indonesia, Sub-Branch Office of Pasuruan City. The research employs a quantitative approach with an associative research design. The population consists of customers who use the BYOND by BSI application, with data collected through questionnaires. Data analysis was performed using multiple linear regression with SPSS version 22. Prior to hypothesis testing, validity and reliability tests were conducted, along with classical assumption tests including normality, multicollinearity, and heteroscedasticity. The results show that usage effectiveness has a positive and significant effect on customer satisfaction, with a t-count value of 3.542 > t-table 1.661 and a significance value of 0.001 < 0.05. Service quality also has a positive and significant effect on customer satisfaction, with a t-count value of 4.334 > t-table 1.661 and a significance value of 0.000 < 0.05. Simultaneously, both variables significantly affect customer satisfaction, as indicated by an F-count value of 286.473 with a significance level of 0.000 < 0.05. The findings confirm that service quality is the most dominant factor in enhancing customer satisfaction compared to usage effectiveness of the application